Knowledge, Stereotypes and the Image of Neighboring Country: A Comparative Study among High School Students from the Finnish-Russian Border Region - Izotova, Nadezda (My University, 2017)
This thesis deals with young people living in the border area and their knowledge about the neighboring country. It investigates attitudes related to the image of the neighboring country among Finnish and Russian high school students from the border region of North Karelia (Finland) and the Republic of Karelia (Russia). The aim of research was to discover relation between students’ personal experience in visiting neighboring country, level of knowledge, stereotyped thinking and image of the neighboring country. The research applied quantitative method of survey. Altogether, there were distributed 222 questionnaires in both countries: 67 in Finland and 155 in Russia among 16 – 17 years old high school students. As a result, research findings indicate that the higher level of knowledge about the neighboring country suggests the lower level of stereotyped thinking towards it. Personal experience in visiting neighboring country has mostly positive impact on absence of stereotyped thinking and biased attitude towards the neighbor. However Russia is still viewed as a threat by the Finnish young people whereas Russian youth see Finland as a friendly and reliable neighbor.